(untitled) (Bangladesh Journal of Botany, 2023)
Burmese grape (Baccaurea sapida Muell. Arg.) belongs to the family Euphorbiaceae, is a minor underexploited fruit crop grown wild as well as under cultivation in Nepal, India, Myanmar, Bangladesh, China, Thailand, for fresh consumption. It is a dioecious plant and reported to have an excellent nutritive value, but mainly grown in homestead condition mostly in neglected ways. The present study was aimed to characterize the germplasm nature, details of flowering and fruiting system of Burmese grape. Tree growth habit and crown shape of all the accessions surveyed were semi erect and irregular, respectively. The colour of the male flowers varied from yellow to green yellow shades while the colour of the female flowers varied from yellow to yellow green and green yellow shades. The variation present on fruit length (2.81 cm to 3.80 cm), fruit weight (12.25g to 22.95g), pulp percentage (49.82% to 65.33%), total soluble solids (9.00º to 13.10ºBrix), tritatable acidity (0.73mg to 1.28mg/100g fruit pulp) and ascorbic acid content ranged from (23.18mg to 57.80mg/100g fruit pulp) suggest suitable selection method for identification of promising Burmese grape genotypes. Bangladesh J. Bot. 52(4): 989-998, 2023 (December)